Development of an experimental single-link flexible manipulator system - Mohd Yatim, Hanim; Zaurah Mat Darus, Intan (International Journal of Engineering and Technology, 2018)
Demand for the applications of flexible manipulator due to their benefits has received attention from the industries. However, the flexibility of flexible manipulator has resulted in structural vibration and needs to be studied accordingly. This paper presents the development of a laboratory facility constituting of single-link flexible manipulator system. A new experimental rig flexible manipulator system constrained to move horizontally was designed, developed and fabricated. The experimental equipment setup and method of capturing data are presented. Experimental works have been done to highlight the effect of forces on hub-angle and end-point vibration of the flexible manipulator. Impact test was carried out to identify the dominant mode of vibration of the flexible manipulator. Result from the impact test was compared with the experimental data recorded for model validation and verification. The experimental result demonstrated that the reasonable accuracy with only 1.31% of error was obtained for the dominant mode of vibration. The experimental rig developed incorporating the sensors and actuators deployed may direct future researchers towards significant applications of flexible manipulator in the industrial sector and to promote better productivity.Â